CLINICAL SIGNIFICANCE OF CALPROTECTIN IN RHEUMATIC DISEASES - A. S. Avdeeva (Научно-практическая ревматология, 2018)
Calprotectin (CP) belongs to the S100 leukocyte protein family, consists of two calcium-binding protein molecules, S100A8 and S100A9 (MRP8/14, calgranulin A/B). MRP8/14 is the main intracellular protein of neutrophil granulocytes and monocytes, which exerts a proinflammatory effect on phagocytes, endothelial cells in vitro and favors the development of the inflammatory process in vivo; it is an important mediator of many regulatory functions, such as chemotaxis; activation of neutrophil degranulation and phagocytosis; inhibition of immunoglobulin synthesis, cell proliferation and differentiation. CP is currently considered as a potential acute-phase marker in many inflammatory and autoimmune diseases. In rheumatoid arthritis (RA), CP maintains chronic inflammation, by activating the endothelium and increasing the migration of neutrophils into the inflamed synovial fluid. A number of studies have demonstrated the role of CP in monitoring RA activity, detecting subclinical inflammation, and predicting disease exacerbations. CP is of great importance in monitoring the efficiency of RA therapy with disease-modifying antirheumatic drugs and biological agents. The value of CP in spondyloarthritis (SpA) is ambiguous: on the one hand, this marker is highly expressed in the synovial tissue of patients with SpA and correlates with the level of acute-phase reactants; on the other hand, its correlation with disease activity indices is very contradictory and requires further clarification. By and large, CP is a promising laboratory marker of great clinical significance.